Isolasi dan Identifikasi Spesies Bakteri Asam Laktat Penghasil Senyawa Antimikrob Asal Kolon Sapi Bali (ISOLATION AND IDENTIFICATION OF LACTIC ACID BACTERIA SPECIES PRODUCING ANTI-MICROBIAL SUBSTANCE ISOLATED FROM COLON OF BALI CATTLE) - Lindawati, Sri Anggreni; Suardana, I Wayan (Jurnal Veteriner, 2017)
Bali cattle as one of the local cattle are known have uniquely genetic characteristics. They are easy toadapt at a less favorable environment, so that they are known as a pioneer cattle. According to theiruniquely, it may allow for the discovery of specific types of acid lactic bacteria compared with others. Thishypothesis is based on the assumption that the types of bacteria as a normal flora in the intestine tract ofcattle are highly dependent on several factors, and one of which is a feed factor. Based on the abovebackground, this study was conducted. The aim of study was to isolate and identify of a specific species oflactic acid bacteria that has anti-microbial substances. The study began by isolation of acid lacticbacteria originated from 20 fecal samples of colon of bali cattle through the growth on selective medium i.e.deMann, Rogosa, Sharpe (MRS) medium followed by Gram staining and catalase test. The screening ofantimicrobial activity of each isolate was performed by culturing of isolates again indicator bacterial on blood agar medium. The selected isolates were continuously tested on medium contains 15% NaCl ,medium with ph 9.6, and medium with temperature 10°C, respectively in order to identification genus ofbacteria. The final stage of identification in order to know the specific isolate, which has antimicrobialsubstances, was confirmated by using the API 50 CHL kit. The results of study showed that one of theisolates that known have widely antimicrobial activities was isolate with 3A code. This isolate hasinhibitory zone to indicator bacterial i.e. Staphylococcus aureus ATCC 29213 and Escherichia coli ATCC25922. This isolate is known as Lactococcus lactis ssp lactis 1 with its similarity value 65.7%. This isolateis potentially to continuously study in order to know the potency of isolate as a probiotic candidate and oras a food preservative.
Keywords: Lactococcus lactis spp lactis 1, antimicrobial substance, colon, Bali cattle